PENGARUH PERSON ORGANIZATION FIT DAN JOB EMBEDEDDNESS TERHADAP TURNOVER INTENTION PADABANK MANDIRI SIDOARJO - yanuar, Dody (Universitas Teknologi Surabaya, 2024)
This study aims to analyze and determine the effect of person Organization fit and job embeddedness on turnover at Bank Mandiri KCP Sidoarjo. Data analysis in this study includes descriptive, research instrument analysis test (validity test and reliability test), multiple linear regression analysis, classical assumption test and hypothesis test. The results of this study indicate that Person Organization Fit and Job Embeddedness simultaneously have a significant effect on the Turnover Intention variable. Person Organization Fit has a significant negative effect on Turnover Intention at Bank Mandiri KCP Sidoarjo. Job embeddedness has a significant negative effect on turnover intention at Bank Mandiri KCP Sidoarjo. The magnitude of the influence of Person Organization Fit and Job Embeddedness simultaneously on Turnover Intention is 0.755 or 75.5%, while the influence of other variables not examined in this study is 24.5%.